Instrumen Sosial Masyarakat Karangmumus Kota Samarinda dalam Penanganan Sampah Domestik - Sudiran, F L (Makara Human Behavior Studies in Asia, 2005)
The scene of the stream area of Karangmumus River is very dirty. Most people here handle the domestic-waste improperly, which make them suffer easily from the epidemic diseases such as: typhus, cholera, and other symptom. The aims of this research are (1) how the society at Karangmumus handles the domestic-waste, (2) how the best way to handle the domestic-waste as a recommendation to the local government, Samarinda city. The method of this research is a case study, use of the description groups. The research is hold in the stream area of Karangmumus River consists the three-sub district Samarinda Utara as station 1, Samarinda Ulu as station 2, and Samarinda Ilir as station 3. It was carried out in September to December 2004. The data collection had been done by questionnaire, which is distributed in three-sub district concerned. The sample is 60% of the population in those three-sub districts by random sampling. The conclusion is based on the questionnaire is that 66,7% of the respondents have bad attitude is handling their domestic-waste. There are some suggestions to handle the domestic-waste: (1) To socialize how to handle domestic-waste properly. (2) To build the temporary places for the domestic-waste. (3) To take the domestic-waste consistently. (4) To complete the equipment to handle the domestic-waste. (5) To train the human resources of the officers concerned. (6) To carry out the law-enforcement on waste regulation through local authority.